Choroba Alzheimera – rola badań immunohistochemicznych w diagnostyce choroby = Alzheimer’s disease - the role of immunohistochemistry in the diagnosis of disease - Cichacz-Kwiatkowska, Beata; Sekita-Krzak, Joanna; Kot-Bakiera, Katarzyna; Jodłowska-Jędrych, Barbara; Wawryk-Gawda, Ewelina (Journal of Education, Health and Sport, 2016)
Cichacz-Kwiatkowska Beata, Sekita-Krzak Joanna, Kot-Bakiera Katarzyna, Jodłowska-Jędrych Barbara, Wawryk-Gawda Ewelina. Choroba Alzheimera – rola badań immunohistochemicznych w diagnostyce choroby = Alzheimer’s disease - the role of immunohistochemistry in the diagnosis of disease. Journal of Education, Health and Sport. 2016;6(2):122-137. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45939 http://ojs.ukw.edu.pl/index.php/johs/article/view/3380 https://pbn.nauka.gov.pl/works/713623 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.01.2016. Revised 12.01.2016. Accepted: 31.01.2016. Choroba Alzheimera – rola badań immunohistochemicznych w diagnostyce choroby Alzheimer’s disease - the role of immunohistochemistry in the diagnosis of disease Beata Cichacz-Kwiatkowska1ABD, Joanna Sekita-Krzak1ABD, Katarzyna Kot‑Bakiera1ABD, Barbara Jodłowska-Jędrych1ABD, Ewelina Wawryk‑Gawda1ABD 1Katedra i Zakład Histologii i Embriologii z Pracownią Cytologii Doświadczalnej, Uniwersytet Medyczny, Lublin, Polska Authors’ Contribution: A Study Design B Data Collection C Statistical Analysis D Manuscript Preparation E Funds Collection Słowa kluczowe: badania immunohistochemiczne, choroba Alzheimera, wewnątrzkomórkowe zwyrodnienia włókienkowe typu Alzheimera, białkowe prekursor amyloidu. Key words: immunohistochemistry, Alzheimer’s disease, neurofibrillary tangles, amyloid precursor protein. Glosariusz: Choroba Alzheimera – najczęstsza postać otępienia, nieuleczalna i postępująca choroba neurodegeneracyjna, po raz pierwszy opisana w 1906 przez Alois Alzheimer [1] Glossary: Alzheimer’s disease (AD), also known as Alzheimer disease, the most common form of dementia, progressive neurodegenerative disease, first described by Alois Alzheimer in 1906 [1] Streszczenie Choroba Alzheimera jest przewlekłą i postępującą chorobą neurodegeneracyjną, będącą zarazem najczęstszą przyczyną zespołu otępiennego. Skutki tej choroby dotykają zarówno samego pacjenta i jego otoczenie, przybierając wymiar zarówno społeczny jak i ekonomiczny. Częstość występowania otępienia towarzyszącego chorobie Alzheimera podwaja się co 4,5 roku u osób po 65. roku życia. U podłoża tego schorzenia leży zróżnicowana grupa zaburzeń związanych ze starzeniem się organizmu oraz interakcjami genetycznymi i środowiskowymi. Procesy neurodegeneracyjne obserwowane w przebiegu choroby Alzheimera prowadzą do upośledzenia morfologicznego i fizjologicznego neuronów oraz w konsekwencji ich śmierci. Doprowadza to bezpośrednio do upośledzenia kontroli poznawczej. W zmienionej patologicznie tkance nerwowej chorych stwierdzono obecność nieprawidłowych struktur, takich jak blaszki amyloidowe i zwyrodnienia włókienkowe (splątki neurofibrylarne). Sformułowano wiele hipotez starających się wyjaśnić procesy prowadzące do neurodegeneracji, najczęściej wymieniana jest teoria kaskady amyloidowej. Metody immunohistochemiczne pozwalają na wykrycie, zlokalizowanie i oznaczenie zmian neurodegeneracyjnych związanych z chorobą Alzheimera. Wykorzystywane są tutaj zarówno przeciwciała poli- jak i monoklonalne, a same badania charakteryzują się dużą czułością i swoistością. Summary Alzheimer’s disease is a chronic, progressive disease, which has been classified as a most frequent causes of dementia in the elderly population. The consequences of this disease affects the patient and his family and have a social and economic dimension. In the population over 65 years of age the incidence of dementias accompanying Alzheimer’s disease doubles every 4.5 years. This disease is caused by a diverse group of genetic and environmental disorders associated with aging of the organism. Neurodegenerative processes seen during the Alzheimer’s Disease result in impairment of neurons morphological and physiological functions causing their death. This leads directly to the impairment of patients cognitive functions. In the pathologically altered nerve tissue the presence of abnormal structures such as amyloid plaques and fibrillar degeneration (neurofibrillary tangles) is revealed. Many hypotheses have been formulated trying to explain the processes leading to neurodegeneration, and the most often mentioned is the amyloid cascade theory. Immunohistochemistry can detect, locate and mark the changes related to the Alzheimer’s disease neurodegeneration. They are used here both poly- and monoclonal antibodies, and the same tests are highly sensitive and specific.